2005
DOI: 10.1111/j.1744-7909.2005.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature Acclimation Pretreatment on the Ultrastructure of Mesophyll Cells in Young Grape Plants (Vitis vinifera L. cv. Jingxiu) Under Cross-Temperature Stresses

Abstract: Leaves from annual young grape plants (Vitis vinifera L. cv. Jingxiu) were used as experimental materials. The ultrastructural characteristics of mesophyll cells in chilling-treated plants after heat acclimation (HA) and in heat-treated plants after cold acclimation (CA) were observed and compared using transmission electron microscopy. The results showed that slight injury appeared in the ultrastructure of mesophyll cells after either HA (38 °C for 10 h) or CA (8 °C for 2.5 d), but the tolerance to subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(62 citation statements)
references
References 17 publications
(12 reference statements)
0
58
0
Order By: Relevance
“…Studies have revealed that specific effects of high temperature on the plant photosynthetic membrane results in the loss of grana stacking or its swelling. In response to heat stress, chloroplasts in the mesophyll cells of grape plants become round in shape, the stroma lamellae become swollen, and the contents of the vacuole form clumps, whilst the cristae were disrupted and mitochondria became empty (Zhang et al, 2005). Such changes result in the formation of antenna-depleted photosystem-II (PS-II) and hence reduced photosynthetic and respiratory activities (Zhang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that specific effects of high temperature on the plant photosynthetic membrane results in the loss of grana stacking or its swelling. In response to heat stress, chloroplasts in the mesophyll cells of grape plants become round in shape, the stroma lamellae become swollen, and the contents of the vacuole form clumps, whilst the cristae were disrupted and mitochondria became empty (Zhang et al, 2005). Such changes result in the formation of antenna-depleted photosystem-II (PS-II) and hence reduced photosynthetic and respiratory activities (Zhang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Membrane fluidity, which is defined as the motion of phospholipid molecules within the lipid bilayer, is influenced by factors such as the interactions of proteins and lipids and ion environments (Huang and Yang 1996). Activation of lipid peroxidation is one of the earliest and nonspecific plasma responses brought by any stress agent, including heat shock (Coote et al 1994;Zhang et al 2005;Liu et al 2006a, b). Interestingly, the MDA assay response obviously decreased in the SA pre-treated leaves, which implies that SA plays an active part in protecting the membrane under heat stress (Fig.…”
Section: The Contribution Of Pm Hmentioning
confidence: 99%
“…Recently, our studies showed that the PM-located phosphatidylinositol-4, 5-bisphosphate (PIP 2 )-specific phospholipase C (PLC) was involved in the SA-mediated signal pathway that leads to the acquisition of heat acclimation-induced thermotolerance and functioned downstream of free SA in cell response to heat acclimation treatment (Liu et al 2006a, b), and the changes in PM H ? -ATPase activities and amounts during the cross adaptation to temperature stresses were also detected using electron microscopic cytochemical assay (Zhang et al 2005). And in pea leaves, the enhanced lipid peroxidation could be one of the causes for the H ?…”
Section: Introductionmentioning
confidence: 99%
“…SSH has successfully been used to identify genes responsive to various biotic and abiotic stresses in various plant species such as Saccharum (Watt 2003); Festuca (Zhang et al 2005); Pennisetum (Mishra et al 2007); Agrostis (Xu et al 2009); Triticum (Chauhan et al 2011). Thus in the current study we focus on identifying, validating and establishing the putative functions of the major differentially expressed genes in P. glaucum during drought stress response using SSH, real-time quantitative qRT-PCR and homology searches.…”
Section: Introductionmentioning
confidence: 99%